Psychometric evaluation of the German Day-to-Day Impact of Vaginal Aging questionnaire using data from two intervention studies. Issue 5 (14th May 2023) - Gabes, Michaela; Donhauser, Theresa; Harder, Anastasia; Masur, Clarissa; Apfelbacher, Christian J.
Abstract : The German version of the Day-to-Day Impact of Vaginal Aging questionnaire showed several adequate measurement properties in two independent intervention studies. It can be used to capture the impact of vulvovaginal atrophy or genitourinary syndrome of menopause symptoms in postmenopausal women. Abstract: Objective: We aimed to further validate the German version of the Day-to-Day Impact of Vaginal Aging (DIVA) questionnaire. Methods: Data were collected in the context of two intervention studies. Forty-two women participated in clinical trial VMP-03/2018 (NCT04222647) and 79 women in clinical trial VFCrC-01/2021 (NCT05211505). Internal consistency was calculated using Cronbach α . Correlations with other outcome measures such as a subjective assessment of symptoms and dyspareunia, the Vaginal Health Index, and the Vaginal Maturation Index were calculated regarding construct validity. A priori hypotheses were formulated for construct validity. Responsiveness was assessed after 43 (±3) and after 38 (±1) days in the two clinical trials. Results: Strong internal consistency in all of the DIVA domains was found ( α ≥ 0.80). Regarding construct validity (at baseline and over time), many hypotheses were confirmed. Furthermore, all of the DIVA domains were able to detect changes over time ( P ≤ 0.006). Moderate to strong effect sizes were found (≥0.460). The data supported the responsiveness of the DIVA. Conclusions: Our findings from two independent intervention studies support internal consistency, construct validity, and responsiveness of the German version of the DIVA (domains).